2017
DOI: 10.1111/bdi.12520
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the experience of auditory verbal hallucinations and accompanying delusions in individuals with a diagnosis of bipolar disorder: A systematic review

Abstract: Clear gaps exist in our current understanding of the first-person experience of AVH in BD and the potential relationship to co-occurring symptoms, including delusions. Further research into cognitive interpretations of AVH in BD might inform adapted psychological interventions for psychotic symptoms in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 86 publications
(402 reference statements)
7
45
0
1
Order By: Relevance
“…Smith et al. have emphasized the need to explore the interplay between psychotic symptoms and mood episodes to better understand auditory hallucinations in BD …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Smith et al. have emphasized the need to explore the interplay between psychotic symptoms and mood episodes to better understand auditory hallucinations in BD …”
Section: Discussionmentioning
confidence: 99%
“…Auditory hallucinations are auditory sensory perceptions, commonly voices or sounds, that occur in the absence of external stimuli. Reports of prevalence rates of auditory hallucinations in bipolar disorder (BD) have varied across studies, but two large studies reported the lifetime prevalence to be 25% in BD type I patients (BDI) and 34% when only BDI patients with psychotic features were included . Auditory hallucinations are reported to be more frequent in manic than in depressed episodes .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations